Low-energy parameters of neutron-neutron scattering - V. A. Babenko; N. M. Petrov (Ядерна фізика та енергетика)
The influence of the mass difference between charged and neutral -mesons on the low-energy parameters of nucleon-nucleon interaction in the spin-singlet state is studied. Using the experimental singlet neutron-proton scattering parameters and the experimental value of neutron-neutron virtual-state energy we obtain the following values for the neutron-neutron scattering length and effective range: . Calculated values of these quantities appear to be in reasonable agreement with the contempo-rary experimental data.